Prefoldin and Pins synergistically regulate asymmetric division and suppress dedifferentiation. - Zhang, Y.; Rai, M.; Wang, C.; Gonzalez, C.; Wang, H. (Scientific reports, 2016)
Prefoldin is a molecular chaperone complex that regulates tubulin function in mitosis. Here, we show that Prefoldin depletion results in disruption of neuroblast polarity, leading to neuroblast overgrowth in Drosophila larval brains. Interestingly, co-depletion of Prefoldin and Partner of Inscuteable (Pins) leads to the formation of gigantic brains with severe neuroblast overgrowth, despite that Pins depletion alone results in smaller brains with partially disrupted neuroblast polarity. We show that Prefoldin acts synergistically with Pins to regulate asymmetric division of both neuroblasts and Intermediate Neural Progenitors (INPs). Surprisingly, co-depletion of Prefoldin and Pins also induces dedifferentiation of INPs back into neuroblasts, while depletion either Prefoldin or Pins alone is insufficient to do so. Furthermore, knocking down either ?-tubulin or ?-tubulin in pins(-) mutant background results in INP dedifferentiation back into neuroblasts, leading to the formation of ectopic neuroblasts. Overexpression of ?-tubulin suppresses neuroblast overgrowth observed in prefoldin pins double mutant brains. Our data elucidate an unexpected function of Prefoldin and Pins in synergistically suppressing dedifferentiation of INPs back into neural stem cells.